The undergraduate research handbook - Wisker, Gina (Bloomsbury study skills, 2019)
This is a comprehensive guide to planning and producing high-quality dissertations, written assignments and project reports at undergraduate level. It supports students of all disciplines through each stage of the research process, from drafting questions and reviewing the literature through to collecting data and presenting their work. It provides practical guidance on common problems, including writer's block and managing deadlines, and contextualises this with examples of real students' experience of research. This text will be invaluable to undergraduate students undertaking academic research in all subject areas. New to this edition Features new and updated content on the internet and critical thinking, and analytical skills in relation to developing and following through with a research agenda.